Zno/Ag Thin Layer Microstructure with The Effect of Annealing Temperature - Sheilla Rully Anggita; Habik Setiawan; Heri Sutanto (Journal of Natural Sciences and Mathematics Research, 2018)
The formation of ZnO/Ag morphology in the form of ganglia structures that are overgrown with grains in previous studies has been shown to degrade the presence of E. coli bacteria. In this research, the variations of annealing temperature were studied, namely 250 ℃, 300 ℃, 350 ℃, and 400 ep when the 4% ZnO/Ag deposition had an effect on crystallinity and morphology. The crystallinity of ZnO/Ag was obtained by using the X-Ray Diffraction (XRD) test and the surface morphology of the ZnO/Ag layer using the Scanning Electron Microscope (SEM) test. The results of the research with the XRD test showed that the crystal structure of ZnO/Ag 4% was hexagonal wurtzite at annealing temperature of 250 ℃ and 300 ℃, while the amorphous structure was obtained in ZnO/Ag with annealing temperature of 350 ℃ and 400 ℃. The largest average crystallite size was owned by ZnO/Ag at annealing temperature of 300 ℃ which was 83.408 µm. The morphology obtained from a thin layer of ZnO/Ag 4% with annealing temperature of 250 ℃ and 300 ℃ is in the form of grains composed of ganglia structures. The ZnO/Ag layer with annealing temperature of 300 ℃ had the largest roughness level of 0.422 µm and the largest surface area of 197.233 µm. Meanwhile, the morphology of ZnO / Ag at annealing temperature of 350 ℃ and 400 ℃ did not form a ganglia structure so that the roughness level was low and the surface area was small. The larger the crystallite size, the higher the roughness level, and the larger the resulting surface area. ©2018 JNSMR UIN Walisongo. All rights reserved.